Amazon River influence on nitrogen fixation and export production in the western tropical north Atlantic - Weber, Sarah Catherine (Georgia Institute of Technology, 2012)
As part of the multidisciplinary ANACONDAS program, we characterized the distributions of nutrients, particulate organic matter, phytoplankton, and stable carbon and nitrogen isotopes in the Amazon plume region during the spring high-flow period of May-June 2010. We encountered the lowest salinities (16.6 psu) near the southern end of our study region where the plume showed the greatest spatial coherence, and the highest salinities (36.0 psu) to the east of the plume. The major nutrients showed distinct patterns of variation with salinity, with NO₃- largely absent from the surface plume and SiO₂ and PO₄³⁻ showing different degrees of conservative behavior. SiO₂ distributions were more strongly conservative, but with clear negative deviations that reflected biological consumption. In contrast, PO₄³⁻ concentrations showed clear positive deviations as large as 0.7 µM across a broad range of salinities as particle- and organically-bound P was released. These nutrient distributions resulted in strong nitrogen limitation and delivery of substantial amounts of SiO₂ and PO₄³⁻ to offshore waters, creating conditions that favored diazotrophy rather than simple eutrophication. We found a variety of diazotrophs in our study area, with interesting regional variation in their distributions. Mesohaline waters to the northwest of the plume axis were strongly dominated by Diatom-Diazotroph Associations (DDAs), particularly the Hemiaulus hauckii Richelia intracellularis association. In contrast, Trichodesmium spp. were most abundant to the southeast of the plume. These two diazotrophs appeared to contribute to the nitrogen and carbon budgets of the upper water column in fundamentally different ways, with H. hauckii making a much greater contribution to the particulate nitrogen pool than Trichodesmium spp. (100% versus 50%, respectively), while contributing to a greater reduction in pCO₂ in the upper water column. These contrasts have important implications for the fate of new production, with DDAs supporting higher export flux ...